THE INTEGRATION OF EXPERIENTIAL TECHNIQUES IN ADULT EDUCATION AND THE FACTORS INFLUENCING THEIR ADOPTION - Angeliki, Gogola; Loukas, Moustakas (International Journal of Research -GRANTHAALAYAH, 2021)
The present research is a quantitative approach to the experiential learning provided in adult education. It focuses on the investigation of the experiential teaching techniques adopted and applied by adult educators at Vocational Training Institutes (VTI), based on their individual and work characteristics. The sample consisted of 317 instructors of public and private VTI, which was a product of inventory sampling, and was conducted at national level. A standard questionnaire, that was prepared for the needs of this research was used as a research tool. The results of the research are presented through descriptive, but also inductive statistical methods and confirm that adult educators use a variety of experiential teaching techniques in their work, with some of them being more preferred than others that seem to be less popular. In addition, the individual-work characteristics of educators affect, in some cases, the degree and intensity with which they utilize some experiential techniques, during the teaching process.